2023
DOI: 10.1001/jamasurg.2022.7055
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Hospital Characteristics Associated With Delayed Diagnosis of Appendicitis

Abstract: ImportanceRacial disparities in timely diagnosis and treatment of surgical conditions exist; however, it is poorly understood whether there are hospital structural measures or patient-level characteristics that modify this phenomenon.ObjectiveTo assess whether patient race and ethnicity are associated with delayed appendicitis diagnosis and postoperative 30-day hospital use and whether there are patient- or systems-level factors that modify this association.Design, Setting, and ParticipantsThis population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
1
10
0
2
Order By: Relevance
“…The diagnoses at the preceding encounters of patients with delay appeared related to the ultimate diagnosis of appendicitis, with abdominal conditions accounting for more than 90%. Regardless of the threshold of certainty used to define delayed diagnosis, the volume-delay association was consistent, and similar to prior estimates 25 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The diagnoses at the preceding encounters of patients with delay appeared related to the ultimate diagnosis of appendicitis, with abdominal conditions accounting for more than 90%. Regardless of the threshold of certainty used to define delayed diagnosis, the volume-delay association was consistent, and similar to prior estimates 25 …”
Section: Discussionsupporting
confidence: 83%
“…Regardless of the threshold of certainty used to define delayed diagnosis, the volume-delay association was consistent, and similar to prior estimates. 25 What can be done to improve diagnostic timeliness for pediatric appendicitis? First, evidence-based abdominal pain protocols for children should be available and applied in all emergency care settings.…”
Section: Discussionmentioning
confidence: 99%
“…It was defined as a previous emergency department or inpatient hospital encounter with an abdominal diagnosis other than appendicitis, and no intervention 7 days prior to subsequent appendectomy encounter. [1][2][3]14 The timing variable (coded as DaysToEvent) was created with the appendectomy encounter day as the day 0. This variable allowed determination of whether a patient had an emergency department or inpatient hospital encounter in the 7 days preceding their appendectomy.…”
Section: Primary Exposurementioning
confidence: 99%
“…In this issue of JAMA Surgery , Reyes et al investigated a number of social determinants of patients with delayed diagnosis of appendicitis by taking a large data set from the Agency for Healthcare Research and Quality and linking it to the State Emergency Department Databases drawn from 4 US states: Florida, Maryland, New York, and Wisconsin. Cases of delayed diagnosis were defined as patients who had been evaluated and discharged from the emergency department in the 7 days preceding an appendectomy.…”
mentioning
confidence: 99%
“…Focusing on race, the study found that Asian/Pacific Islander patients, Hispanic patients, non-Hispanic White patients, and other races had similar rates of delayed diagnosis, whereas non-Hispanic Black patients had a 41% higher rate of delayed diagnosis, independent of the other social determinants evaluated in the study . The robustness of this finding was confirmed in rigorous post hoc sensitivity analysis using first a cohort of patients with low comorbidities and again on another cohort of patients with private insurance in high-income areas.…”
mentioning
confidence: 99%